KERJA SAMA INDONESIA - SINGAPURA DALAM BIDANG EKONOMI DIGITAL: Studi Kasus MoU Capacity Building on E-commerce Logistics Periode 2018-2020 - Achbil Khumaini Fajrin Muhammad, (2024)
This research aims to analyze the cooperation carried out by Indonesia and Singapore in the MoU: Capacity Building on e-Commerce Logistics in Indonesia. This research uses theories and concepts such as bilateral cooperation, digital economy, capacity building and also e-commerce logistics. This research uses descriptive qualitative methods with primary and secondary data sources through interviews with the Ministry of Economic Coordination, Pt. Pos Indonesia related documents, previous research, and articles. This research argues that Indonesia is still far behind its neighboring countries in the digital economy in the e-commerce logistics sector. By issuing policies, such as the National Electronic Trading System Roadmap, and establishing cooperation with Singapore in the field of digital economic skills training and e-commerce logistics using capacity building methods. It is hoped that the logistics e-commerce industry in Indonesia can develop and strengthen the digital economy. Singapore is a strategic cooperation partner because it has good digital quality and strong bilateral relations with Indonesia. With joint efforts, Indonesia can become a leader in the digital economy in Southeast Asia.